Educational and Wealth Inequalities in Smokeless Tobacco Use: An Analysis of Rural-Urban Areas of Bangladesh and India. (January 2019) - Bandyopadhyay, Anupam; Irfan, Mohd
This study aims to investigate the educational and wealth inequalities in smokeless tobacco (SLT) use in rural and urban areas of Bangladesh and India, the 2 largest global SLT users. Using the Global Adult Tobacco Survey, both absolute and relative measures of inequality were estimated. The analysis reveals that the educational inequalities in SLT use were higher in urban areas of India and in rural areas of Bangladesh, whereas the wealth inequalities in SLT use were higher in urban areas of both the countries. Moreover, the logit model showed that the odds of SLT use declined with an increase in the level of education and wealth in rural and urban areas of India. However, no consistent pattern was observed in rural and urban areas of Bangladesh. The findings clearly delineate the subgroups which require immediate attention for SLT cessation interventions in these 2 countries.